Effect of lanthanum additive on electrical and thermal properties of bismuth sodium titanate ceramics - P. Eaksuwanchai (2018)
This work investigated the preparation and properties of (Bi0.5Na0.5)1-1.5xLaxTiO3ceramics where x = 0, 0.05, 0.10, 0.15 and 0.20 mol fraction. The powders were fabricated by mixed oxide method and calcined at 800°C for 2 h. The ceramic pellets were prepared by uniaxial pressing method and being sintered at various temperatures ranging from 1150-1200°C for 2 h. Bulk densities, phase, electrical and thermal properties were also measured using various techniques. The result showed that all ceramic samples possessed high density and XRD patterns indicated that all ceramics had a main phase of BNT-based composition with rhombohedral (or pseudocubic) structure. The formation of secondary phase was found for sample containing La greater than 0.10 mol fraction. Electrical resistivity measurements at low frequencies indicated a decreasing trend with increasing La addition indicating an increase in electronic conduction. The dielectric constant and thermal conductivity measurements also showed the effects of charged defects induced by La addition and macro defects present by the formed second phase in this material system. © 2013 Copyright Taylor and Francis Group, LLC.